2020
DOI: 10.3390/electronics9040630
|View full text |Cite
|
Sign up to set email alerts
|

LoRaWAN Networking in Mobile Scenarios Using a WiFi Mesh of UAV Gateways

Abstract: Immediately after a disaster, such as a flood, wildfire or earthquake, networks might be congested or disrupted and not suitable for supporting the traffic generated by rescuers. In these situations, the use of a traditional fixed-gateway approach would not be effective due to the mobility of the rescuers. In the present work, a double-layer network system named LoRaUAV has been designed and evaluated with the purpose of finding a solution to the aforementioned issues. LoRaUAV is based on a WiFi ad hoc network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Several studies have shown the possible adoption of LoRa-based protocols (e.g., Lo-RaWAN) for UAV communications, with different long-range applications, implementations, and use cases. A preliminary use of LoRaWAN is discussed in [19], where multiple UAVs are used as flying LoRaWAN gateways (GWs) to provide a network coverage to ground LoRaWAN-based end nodes and to exploit LoRaWAN only for ground-to-UAV applications in emergency-like situations while the backbone network relies on Wi-Fi (assuming LOS links). A similar approach is presented in [20], where multiple flying UAVs, each one equipped with a LoRaWAN GW, cooperate to form a complex LoRaWANoriented urban surveillance system to provide efficient and selective network coverage.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the possible adoption of LoRa-based protocols (e.g., Lo-RaWAN) for UAV communications, with different long-range applications, implementations, and use cases. A preliminary use of LoRaWAN is discussed in [19], where multiple UAVs are used as flying LoRaWAN gateways (GWs) to provide a network coverage to ground LoRaWAN-based end nodes and to exploit LoRaWAN only for ground-to-UAV applications in emergency-like situations while the backbone network relies on Wi-Fi (assuming LOS links). A similar approach is presented in [20], where multiple flying UAVs, each one equipped with a LoRaWAN GW, cooperate to form a complex LoRaWANoriented urban surveillance system to provide efficient and selective network coverage.…”
Section: State-of-the-artmentioning
confidence: 99%
“…In detail, the authors discussed their experimental results in a range between 0 m and 60 m, with a maximum effective 1-hop range of approximately 130 m. Nevertheless, their architecture requires multiple GWs connected with a ground control center, thus remaining a ground mesh network with no aerial part. A simulated doublelayer mesh network, designed and evaluated for disaster recovery scenarios, was proposed in [19], where UAVs act as GWs in a Wi-Fi ad hoc network for the traffic generated between mobile LoRaWAN nodes and a remote ground station. Similar to other works, even in this case, the only available network among the flying drones is based on the Wi-Fi protocol, thus limiting the maximum distance between flying drones.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Meanwhile, recently, the studies in which the authors suggest UAVs be used for improving the performance or enabling new functionalities within LoRaWAN have started to appear. Specifically, in [10], the UAVs are used to charge the LoRaWAN devices, and in [11]- [13], the UAVs are used to collect the data from LoRa and LoRaWAN sensors. In [11], the authors investigate how a drone-based gateway (GW) can improve the reliability of LoRaWAN communication in urban scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…In [12], the authors assess how much can a drone increase the coverage of the network. The author of [13] investigates how to use the groups of UAV-based LoRaWAN GWs to improve the data delivery reliability. Nonetheless, to the best of our knowledge, none of the current studies focuses on the LoRaWAN end device energy consumption and lifetime improvements enabled by the UAV GWs.…”
Section: Related Workmentioning
confidence: 99%
“…Recent times have witnessed a wide range of applications for unmanned aerial vehicles (UAVs) including the commercial, military, and research fields [1][2][3][4][5]. Most of the autonomous UAV flight missions are limited to cruise on a predefined path with steady flight states.…”
Section: Introductionmentioning
confidence: 99%